Real-World Experience of Methotrexate in the Treatment of Skin Diseases: an Italian Delphi Consensus - Giovanni Damiani; Paolo Amerio; Federico Bardazzi; Carlo G. Carrera; Andrea Conti; Francesco Cusano; Paolo Dapavo; Clara DeSimone; May El Hachem; Gabriella Fabbrocini; Paolo Gisondi; Francesco Loconsole; et al. (Adis, Springer Healthcare, 2023)
Abstract Background After decades of use, methotrexate displays an established safety and efficacy profile in both in-hospital and outpatient settings. Despite its widespread use, there is surprisingly little clinical evidence to guide daily practice with methotrexate in dermatology. Objectives To provide guidance for clinicians in daily practice for areas in which there is limited guidance. Methods A Delphi consensus exercise on 23 statements was carried out on the use of methotrexate in dermatological routine settings. Results Consensus was reached on statements that cover six main areas: (1) pre-screening exams and monitoring of therapy; (2) dosing and administration in patients naïve to methotrexate; (3) optimal strategy for patients in remission; (4) use of folic acid; (5) safety; and (6) predictors of toxicity and efficacy. Specific recommendations are provided for all 23 statements. Conclusions In order to optimize methotrexate efficacy, it is essential to optimize treatment using appropriate dosages, carrying out a rapid drug-based step-up on a treat-to-target strategy and preferably using the subcutaneous formulation. To manage safety aspects appropriately, it is essential to evaluate patients' risk factors and carry out proper monitoring during the course of treatment.